VASOMOTOR FUNCTION OF THE ENDOTHELIUM IN PATIENTS WITH CHRONIC KIDNEY DISEASE AND HYPERTENSION - N. V. Demikhova; M. A. Vlasenko; E. Kurshubadze; V. A. Sukhonos (Ukrainian Journal of Nephrology and Dialysis, 2017)
Investigation of the functional state of the vascular endothelium contributes to the further study of the mechanisms of development and pharmacological correction, particularly in hypertensive patients with chronic kidney disease.Material and Results. The study involved 172 patients with arterial hypertension (AH) in patients with chronic kidney disease. In the study of vascular-motor response to decompression and test with nitroglycerin in 60% of cases occur reduced vasodilatory and in 12.6% constrictor response. Normal character of vasodilation was 27.4%. Endothelium-independent vasodilation in the brachial artery decompression was reduced by 51.1% compared with the control. The growth of endothelium-independent vasoconstriction in the degree III AH was reduced to a lesser degree than the endothelium dependent - by 6.5% and 19.4% (p<0.01), respectively.Conclusion. Thus impaired endothelium-mediated autoregulation of vascular tone in hypertensive patients with chronic kidney disease is an important element in the pathogenesis of high blood pressure as one of major adaptation mechanisms.